Strengthening Effect of Rupiah Exchange Rate Through Financing Dimension on Profitability in Islamic Commercial Banks in Indonesia - Nawasiah, Nana; Derriawan, Derriawan; Sari, Lola Fitria; Merawati, Endang Etty; Khairina, Putri Rana (Magister Akuntansi Universitas Pancasila, 2025)
Purpose: This study analyzes the impact of exchange rates on the financial health of Islamic Commercial Banks (BUS) in Indonesia, focusing on the financing dimension.Methodology: The study employs the Moderated Regression Analysis (MRA) method to assess the interaction between exchange rates (independent variable), NPF and FDR (moderator variables), and ROA (dependent variable). It uses secondary data from the financial statements of eight Islamic Commercial Banks from 2020 to 2022, comprising 36 observations.Finding: The results indicate that exchange rates significantly impact ROA, both directly and through interactions with NPF and FDR. The model has an adjusted R² of 34.89% and an RMSE of 1.1573, demonstrating good quality. The F-test value is 5.69 with a probability of 0.0015 (<0.05). The regression assumptions confirm normality and homoscedasticity; however, the Durbin-Watson test (1.48 < 1.80) indicates autocorrelation.Implication: This study recommends strengthening risk management in Islamic banks through Sharia-based financing principles. It uniquely contributes to Islamic banking research by exploring exchange rate effects using a three-way interaction approach.Originality: This study provides a unique contribution in analyzing the effect of exchange rates on the health of Islamic banks through a three-way interaction approach, which has not been widely discussed in the context of Islamic banking in Indonesia.